Practice Towards Storage of Unused and Disposal of Expired Medicines among Households in Dharan, Nepal - Chaudhary, Aswani; Karki, Sandip; Baral, Yogendra; Dahal, Prakash; Aryal, Bijaya (Nepal Journal of Health Sciences, 2024)
Introduction: Improper disposal of unused medications has been a public health problem, as unused drug adversely effects on health and environment. Objective: The main objective of this study was to assess the extent of unused medications disposal knowledge, attitude, and practice of among household in Dharan, Province 1, Nepal. Methods: A survey based descriptive study was used. Households were conveniently selected and interviewed using structured questionnaires. Attitudes and practices regarding medicine disposal and storage were asked. The data were analyzed by SPSS version 20.0 software and presented descriptively. Results: Among 380 household surveyed, majority of respondents (82%) reported storing unused medications in their home and only 5% reported returning medication to a pharmacy. Predominant reason for medication non-used was disease or symptoms felt improved (80 %). Less than half of respondents (45%) had check the expiry date of their medicine before purchasing. Most respondents (88%) thought that improper disposal of medicine may cause harmful effects to health and environment. Conclusion: Incorrect practices were found in Dharan families with regard to the storage and disposal of unused medications. Along with a comprehensive media campaign to inform consumers about safe medication disposal techniques, an efficient method for disposing of leftover medications should be offered. This system should be supported by local pharmacist.